2005
DOI: 10.1029/2004jd005236
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the chemistry of ship emission plumes during ITCT 2002

Abstract: [1] A ship emission plume experiment was conducted about 100 km off the California coast during the NOAA Intercontinental Transport and Chemical Transformation (ITCT) 2K2 airborne field campaign. Measurements of chemical species were made from the NOAA WP-3D aircraft in eight consecutive transects of a ship plume around midday during 2.5 hours of flight. The measured species include NO x , HNO 3 , peroxyacetylnitrate (PAN), SO 2 , H 2 SO 4 , O 3 , CO, CO 2 , nonmethane hydrocarbons (NMHC), and particle number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
187
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(201 citation statements)
references
References 65 publications
11
187
3
Order By: Relevance
“…This is in general agreement with previously reported ambient measurements of 0.5-2 ppbv NO x in ship plumes in the northern hemisphere. [32] Isoprene was emitted into the model by daylight in keeping with previous observations [3] to reach the levels measured during the cruise (see Table 1). Bloom emissions occurred for 4 consecutive days starting on 31 January at 0000 hours local time.…”
Section: Local Photochemical Effects Of Ships and Phytoplanktonmentioning
confidence: 99%
“…This is in general agreement with previously reported ambient measurements of 0.5-2 ppbv NO x in ship plumes in the northern hemisphere. [32] Isoprene was emitted into the model by daylight in keeping with previous observations [3] to reach the levels measured during the cruise (see Table 1). Bloom emissions occurred for 4 consecutive days starting on 31 January at 0000 hours local time.…”
Section: Local Photochemical Effects Of Ships and Phytoplanktonmentioning
confidence: 99%
“…This filter was applied because of the detection limit of SO 2 on the order of a few hundred pptv. The error in the OH calculation was shown to be smaller than a factor of 2 [Chen et al, 2005]. The H 2 SO 4 steady state model calculation will be described in more detail elsewhere (A. T. Hanks et al, manuscript in preparation, 2010).…”
Section: Warneke Et Al: Biogenic Emissions and Inventoriesmentioning
confidence: 99%
“…For this analysis, the value of the mass accommodation coefficient used was 0.7 as suggested by Chen et al [2005]. OH concentrations were only calculated for sulfur dioxide concentrations larger than 1 ppbv using equation (5).…”
Section: Warneke Et Al: Biogenic Emissions and Inventoriesmentioning
confidence: 99%
“…Several studies with Lagrangian models (e.g. von Song et al, 2003;Chen et al, 2005) showed that the NO x lifetime within ship plumes is a factor 2.5-10 shorter than the lifetime of roughly 1 day estimated by the instantly diluting CTMs. These Lagrangian models account for the higher NO x concentrations in the initial dispersion stages of the plume, leading to elevated OH levels and thereby shorter NO x lifetimes.…”
Section: Introductionmentioning
confidence: 99%